2015
DOI: 10.1016/j.jelekin.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Does insertion of intramuscular electromyographic electrodes alter motor behavior during locomotion?

Abstract: Intramuscular electromyography (EMG) is commonly used to quantify activity in the trunk musculature. However, it is unclear if the discomfort or fear of pain associated with insertion of intramuscular EMG electrodes results in altered motor behavior. This study examined whether intramuscular EMG affects locomotor speed and trunk motion, and examined the anticipated and actual pain associated with electrode insertion in healthy individuals and individuals with a history of low back pain (LBP). Before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…In fact, participants in our study reported low pain levels despite the insertion and presence of intramuscular electrodes during muscle performance tests. Our results agree with the findings by Armour Smith and Kulig who also reported minimal pain perception during walking (<1/10) after intramuscular EMG electrode insertion [16]. The low pain levels experienced by our participants likely contributed to the similar muscle performance obtained during all 3 conditions of our experiment.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In fact, participants in our study reported low pain levels despite the insertion and presence of intramuscular electrodes during muscle performance tests. Our results agree with the findings by Armour Smith and Kulig who also reported minimal pain perception during walking (<1/10) after intramuscular EMG electrode insertion [16]. The low pain levels experienced by our participants likely contributed to the similar muscle performance obtained during all 3 conditions of our experiment.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research has found that anticipated pain, more than actual pain, correlated with altered movement [29]. Related to the current study, Armour Smith and Kulig assessed the anticipated and actual pain levels associated with fine‐wire EMG insertion during walking tasks [16]. They found no significant difference in trunk mechanics during walking, and that low pain levels were reported throughout for both anticipated and actual pain levels [16].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Additionally, fine wire electrodes have been proposed as impractical and difficult to use in some contexts because of their invasiveness and potential for discomfort (Rudroff, 2008). Although discomfort is possible and varies depending on the type and intensity of the contraction, recent work has shown that the use of fine wire intramuscular electrodes are associated with minimum discomfort during motor control tasks, <1 out of 10 on the visual analogue scale (Armour Smith & Kulig, 2015).…”
Section: Intramuscular Electrodesmentioning
confidence: 99%